Предмет: Алгебра,
автор: Magammed2272
Даны выражения 5c(c+2) и 4с(с-4)сравните их при значении с=-3
Ответы
Автор ответа:
0
5с^2+10с=5*9+2=47
4c^2-16c=4*9-16*(-3)=84
4c^2-16c=4*9-16*(-3)=84
Автор ответа:
0
При с = - 3
первое выражение: 5c^2 + 10c = 5*9 + 10*(-3) = 45 - 30 = 15
второе выражение: 4 * (-3) (-3 - 4) = - 12 * - 7 = 84
84 > 15
Значит 5с(с +2) < 4c (c -4)
первое выражение: 5c^2 + 10c = 5*9 + 10*(-3) = 45 - 30 = 15
второе выражение: 4 * (-3) (-3 - 4) = - 12 * - 7 = 84
84 > 15
Значит 5с(с +2) < 4c (c -4)
Похожие вопросы
Предмет: Математика,
автор: zhannakurchenko34
Предмет: Математика,
автор: marrgii
Предмет: Математика,
автор: derkachnastia2009
Предмет: Математика,
автор: LoolooFox